Screening of Morus alba, Citrus litnon and Trigonella foenum-graecum extracts for antimicrobial properties and phytochemical compounds - Sheikhlar, Atefeh; Alimon, Abdul Razak; Mohd Daud, Hassan; Saad, Che Roos; Shanagi, H. (Asian Network for Scientific Information, 2013)
In the present study, the effect of aqueous and methanol extracts of Trigonella foenum-graecum seed (fenugreek), Citrus limon peel (lemon) and Morus alba foliage (mulberry) against two Gram- negative bacteria, Aeromonas hydrophila and Escherichia coli and two Gram-positive bacteria, Streptococcus agalactiae and Staphylococcus aureus were investigated and the phytochemical compounds of the tested herbal extracts were determined. The results indicated that the aqueous extracts of Trigonella foenum-graecum seed and Citrus limon peel revealed weak antibacterial activity against the bacteria. The methanol extracts of all herbs exhibited stronger antimicrobial activities against the tested pathogens. Among the entire methanol extracts, the Morus alba had the strongest activities. Aeromonas hydrophila was the most sensitive microorganism tested. The phytochemical screening of the plants showed the presence of secondary metabolites such as phenols, volatile oils, tannins, saponins, steroids, flavonoid, terpenoids and alkaloids.